MATH SOLVE

4 months ago

Q:
# (6x^3+x^5+2x^2−7−4x)−(3x^2−5x+2+5x^5+3x^4)

Accepted Solution

A:

Let's simplify step-by-step.6x3+x5+2x2−7−4x−(3x2−5x+2+5x5+3x4)

Distribute the Negative Sign:=6x3+x5+2x2−7−4x+−1(3x2−5x+2+5x5+3x4)=6x3+x5+2x2+−7+−4x+−1(3x2)+−1(−5x)+(−1)(2)+−1(5x5)+−1(3x4)=6x3+x5+2x2+−7+−4x+−3x2+5x+−2+−5x5+−3x4

Combine Like Terms:=6x3+x5+2x2+−7+−4x+−3x2+5x+−2+−5x5+−3x4=(x5+−5x5)+(−3x4)+(6x3)+(2x2+−3x2)+(−4x+5x)+(−7+−2)= −4x5+−3x4+6x3+−x2+x+−9

Answer:= −4x5−3x4+6x3−x2+x−9

Distribute the Negative Sign:=6x3+x5+2x2−7−4x+−1(3x2−5x+2+5x5+3x4)=6x3+x5+2x2+−7+−4x+−1(3x2)+−1(−5x)+(−1)(2)+−1(5x5)+−1(3x4)=6x3+x5+2x2+−7+−4x+−3x2+5x+−2+−5x5+−3x4

Combine Like Terms:=6x3+x5+2x2+−7+−4x+−3x2+5x+−2+−5x5+−3x4=(x5+−5x5)+(−3x4)+(6x3)+(2x2+−3x2)+(−4x+5x)+(−7+−2)= −4x5+−3x4+6x3+−x2+x+−9

Answer:= −4x5−3x4+6x3−x2+x−9